(untitled) (International relations and international law Journal, 2016)
The article is devoted to one of the most pressing problems of the ensuring thechildren’s rights and safety in armed conflict. Children – one of the most vulnerable people’s categories on Earth. Childhood and war – incompatible concepts. Special protection of children is provided on the basis of characteristic preferential treatment to children in armed conflicts because of their vulnerability, especially sex and age. It is a comprehensive series of measures that aim to ensure that children do not feel any additional suffering during the war, which may be associated with their physiological characteristics or other factors inherent in this group. The studies of the topic the author analyzes the current situation in the sphere of protection of child rights in armed conflicts, consider the normative aspect of international participation in Kazakhstan are invited to complete and adopt a special legal acts in the field of ensuring the rights and safety of children in armed conflicts.